Marketing management - Kotler, Philip (New Delhi : Prentice-Hall of India, 2001)
Business
2002-07-24
Keywords: Marketing management; Customer satisfaction; Markets; Strategic planning; Marketing opportunities; Marketing environment; Consumer markets; Buyer behavior; Business markets